Risk management and business continuity in public hospitals: the case study of tawam Hospital United Arab Emirates (UAE - Almansoori, Ahmed Saif (2023)
Despite the substantial amount of research in risk management, there is no clear evidence for any research or study that has investigated risk management and business continuity in UAE public hospitals, specifically the Tawam Hospital UAE. Therefore, the current study aims to investigate the impact of risk management culture, risk management process, and risk management governance on the business continuity of public hospitals in the UAE. The data were collected through a questionnaire distributed to 600 respondents, of which 297 (49.5 per cent) were successfully retrieved. Among the retrieved questionnaires, 24 were unusable due to either partial filling by the respondents or multiple options on some questions. Data was collected through a questionnaire approach where a valid sample of this brought the total usable questionnaire to 273 responses that have been tested empirically, representing 45.5 per cent of the total questionnaire originally administered. Moreover, the study findings reveal that there is a significant mediating effect of management commitment on the relationship between risk management process and business continuity. Finally, the quantitative analysis through survey questionnaires technique also reveal that personal factors, social factors, and environmental factors are major indicators for the business continuity in the Tawam Hospital. From the result, it is shown that collectively the three exogenous constructs explained less than 1% variability in management commitment towards business continuity in Tawam Hospital UAE. Therefore, the risk management practices of the study (risk management culture, risk management process, and risk management governance) along with the mediator management commitment are essential to improve risk management in public hospitals in the UAE. Besides, the final model of the study can be used to replicate the investigation in other contexts such as private hospitals or other organizations since it provided insightful understanding for the risk management in public health organization in the UAE.